2021
DOI: 10.3390/agronomy11050853
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptome and Metabolome Analysis Reveals an Essential Role for Auxin in Hypocotyl Elongation during End-of-Day Far-Red Treatment of Cucurbita moschata (Duch. Ex Lam.)

Abstract: Long, robust hypocotyls are important for facilitating greenhouse transplant production. The use of far-red light at the end of the day (end-of-day far-red, EOD-FR) is known to prompt hypocotyl elongation, but the mechanism of EOD-FR-mediated hypocotyl elongation in pumpkin remains unclear. Here, we found that hypocotyl length, parenchymal cell size in hypocotyls, and plant IAA levels were significantly greater in pumpkin after EOD-FR treatment. This effect was counteracted by the application of the polar auxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Consistent with the small phenotypic effects, supplemental FR also triggered a very mild transcriptome response as compared to studies in other species (Gommers et al, 2017;Liu et al, 2021;Pantazopoulou et al, 2017;Kohnen et al, 2016). Additionally, in our study, even that small number of responsive genes is not the same between the varieties.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the small phenotypic effects, supplemental FR also triggered a very mild transcriptome response as compared to studies in other species (Gommers et al, 2017;Liu et al, 2021;Pantazopoulou et al, 2017;Kohnen et al, 2016). Additionally, in our study, even that small number of responsive genes is not the same between the varieties.…”
Section: Discussionsupporting
confidence: 90%
“…Numerous researchers have investigated the effects of different wavelengths of light on plant growth and development [12,13]. However, less attention has been paid to end-of-light (EOD) and most of the existing studies on EOD have focused on the phenomenon that R/FR changes the morphology of photosensitive pigments (Pr/Pfr) to the extent that it affects the growth of plant hypocotyls [14][15][16][17], and little research has been conducted on the end-of-day additive effects of the remaining light qualities.…”
Section: Introductionmentioning
confidence: 99%
“…EOD FR-treated tomato ( Solanum lycopersicum ) plants grew higher [ 22 ]. Liu et al [ 23 ] showed that auxin plays an essential role in the EOD FR light-mediated hypocotyl elongation of pumpkin ( Cucurbita moschata ), shedding light on the mechanisms of EOD FR mediated hypocotyl elongation. The EOD R light led to a higher mass of dill ( Anethum graveolens ) plants.…”
Section: Introductionmentioning
confidence: 99%